2016
DOI: 10.1080/09540105.2016.1228838
|View full text |Cite
|
Sign up to set email alerts
|

Severity of atopic dermatitis in relation to food and inhalant allergy in adults and adolescents

Abstract: The aim of this study is the evaluation of the relationship between the severity of atopic dermatitis (AD) and the occurrence of IgEmediated food allergy, food sensitization, and sensitization to inhalant allergens. The complete dermatological and allergological examinations were performed and the severity of AD was evaluated with the SCORing Atopic Dermatitis index. The statistical evaluation of the relationship between the occurrence of IgE-mediated food allergy, food sensitization, sensitization to inhalant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Patients suffering from moderate and severe forms of AD suffer significantly more often from sensitization to mites, animal dander, dust and feather in comparison to patients with mild form of AD (Celakovska & Bukac, 2017b), (Table 1 the rising occurrence of sensitization to inhalant allergens). A significant relation was also found between the severity of AD and the occurrence of early, combined and late IgE-mediated food allergy reaction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients suffering from moderate and severe forms of AD suffer significantly more often from sensitization to mites, animal dander, dust and feather in comparison to patients with mild form of AD (Celakovska & Bukac, 2017b), (Table 1 the rising occurrence of sensitization to inhalant allergens). A significant relation was also found between the severity of AD and the occurrence of early, combined and late IgE-mediated food allergy reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of food sensitization to cow's milk, wheat, egg white and yolk, soy and peanuts is not in significant relation to the severity of AD (patients with positive results of sIgE and/or SPT and/or APT without the clinical symptoms) (Celakovska & Bukac, 2017b), (Table 2). Regarding the relation between the food hypersensitivity reactions and the severity of AD, we confirmed that patients with AD and food hypersensitivity reactions suffer significantly more often from moderate and severe forms of AD (Celakovska & Bukac, 2015b), ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies have shown that similarly to other atopic diseases such as asthma and allergic rhinitis, AD patients have increased aeroallergen sensitization . However, scarce literature is available that evaluates the association between exposure to indoor allergens like house dust mite (HDM), pet dander, and fungi, with AD severity . Nowadays, multiparametric methods have been developed that permit the simultaneous detection of multiple allergens in a single dust sample, with high sensitivity and specificity, as well as an excellent interassay reproducibility .…”
Section: Introductionmentioning
confidence: 99%